Глава 9. Основы единой теории движителей на непрерывных потоках. Вывод формул тяги, полетного (тягового) КПД, теоремы о подъемной силе продуваемого изолированного профиля единичного размаха, как движителя на непрерывных потоках (краткая теория крыла самолета) - Мамедов, Б. Ш. (My University, 2012)
Рассматриваются недостатки современной теории воздушно-реактивных двигателей, связанные с ошибочной теоремой о подъемной силе продуваемого профиля, выведенной профессором Н. Е. Жуковским в 1912 г.

Are looked through the drawbacks of modern theory of air-jet engines, which are connected with a mistaken theorem of the rising force of blowing profile, calculated by professor N. J. Gukovsky in 1912 year
Chapter 9. Foundations of unit theory of movers on continuous flows. Calculation of formulas of thrust, flying (thrust) efficiency, theorem of the rising force of the blowing isolated profile of unit range, as a mover on continuous flows (short theory of aircraft wing)
Keywords: кинематический анализ; теория воздушно-реактивных двигателей; авиадвигателестроение; газодинамическая устойчивость; blowing profile; kinematical analyse; thrust of blowing profile; theorem of rising force